2019
DOI: 10.3390/insects10050133
|View full text |Cite
|
Sign up to set email alerts
|

Sex Ratio of Small Hive Beetles: The Role of Pupation and Adult Longevity

Abstract: The sex ratio of sexually reproducing animal species tends to be 1:1, which is known as Fisher’s principle. However, differential mortality and intraspecific competition during pupation can result in a biased adult sex ratio in insects. The female-biased sex ratio of small hive beetles (SHBs) is known from both laboratory and field studies, but the underlying reasons are not well understood. Here, we used laboratory mass and individual pupation to test if differential mortality between sexes and/or intraspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Substrate type also proved to be an important factor in determining differences between male and female abundances in the Spring of the Bijela rijeka River (CRO) (p = 0.001, p ≤ 0.001) and upper reach of the Bijela rijeka River (p = 0.001, p ≤ 0.001), as shown in Figure 8. Elliot [86], in his study of four elmid species, found that the sex ratio was 1:1 according to Fisher's principle [91,92], a result that was also found for E. bosnica in the Spring of the Bistrica River. In the other springs and habitats studied, however, the ratio was in favor of males, especially in the winter months; this could be explained by the emergence of females in summer [88,89].…”
Section: Population Traits and Seasonal Dynamicsmentioning
confidence: 73%
See 1 more Smart Citation
“…Substrate type also proved to be an important factor in determining differences between male and female abundances in the Spring of the Bijela rijeka River (CRO) (p = 0.001, p ≤ 0.001) and upper reach of the Bijela rijeka River (p = 0.001, p ≤ 0.001), as shown in Figure 8. Elliot [86], in his study of four elmid species, found that the sex ratio was 1:1 according to Fisher's principle [91,92], a result that was also found for E. bosnica in the Spring of the Bistrica River. In the other springs and habitats studied, however, the ratio was in favor of males, especially in the winter months; this could be explained by the emergence of females in summer [88,89].…”
Section: Population Traits and Seasonal Dynamicsmentioning
confidence: 73%
“…Substrate type also proved to be an important factor in determining differences between male and female abundances in the Spring of the Bijela rijeka River (CRO) (p = 0.001, p ≤ 0.001) and upper reach of the Bijela rijeka River (p = 0.001, p ≤ 0.001), as shown in Figure 8. Elliot [86], in his study of four elmid species, found that the sex ratio was 1:1 according to Fisher's principle [91,92], a result that was also found Although the sex ratio is known as one of the key parameters for knowing the biology of any species, there are few data in the literature on Elmidae [86,[88][89][90]. Sex ratios of E. bosnica in four studied karst springs differed at spatial and temporal scales (Table 3).…”
Section: Population Traits and Seasonal Dynamicsmentioning
confidence: 99%
“…We did this on purpose, even though there were ways to determine the BMIs for each sex and link them to mortality. Since the sex ratio of an individual tends to be fairly equal according to Fisher’s principle [ 61 ], we assumed that when farmers culture grasshoppers on a large scale, both males and females would be present in roughly equal ratios in the rearing cabinets [ 62 ]. In contrast, by displaying BMI data separately for males and females and linking them with mortality, it would encounter difficulties in associating space with BMI for a species, as the dual BMI (male and female independently) does not accurately reflect reality in culture cabinets since both sexes present there in almost equal force simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, freshly hatched SHB larvae were fed by providing them with a honey bee worker brood frame until they had reached the post-feeding wandering stage and then transferred into a 473 mL glass jar filled with suitable autoclaved soil for pupation. Pupation containers were kept at 25 • C, 80% RH, 24 h dark until adult emergence [46]. Upon emergence, adult SHBs [N = 10] were kept in incubators with sugar water [45] for seven days and then freeze killed for further chemical analysis.…”
Section: Experimental Designmentioning
confidence: 99%